2017
DOI: 10.1038/tp.2016.275
|View full text |Cite
|
Sign up to set email alerts
|

A methylome-wide mQTL analysis reveals associations of methylation sites with GAD1 and HDAC3 SNPs and a general psychiatric risk score

Abstract: Genome-wide association studies have identified a number of single-nucleotide polymorphisms (SNPs) that are associated with psychiatric diseases. Increasing body of evidence suggests a complex connection of SNPs and the transcriptional and epigenetic regulation of gene expression, which is poorly understood. In the current study, we investigated the interplay between genetic risk variants, shifts in methylation and mRNA levels in whole blood from 223 adolescents distinguished by a risk for developing psychiatr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 57 publications
0
28
0
Order By: Relevance
“…There is also an increasing number of genome-wide DNAm profiling studies of non-central nervous system (CNS) tissues such as blood (12,13,(48)(49)(50)(51)(52)(53) and saliva (54) ( Table 2). These can be further subdivided into longitudinal studies (48)(49)(50)(51)54), which assessed markers of conversion to psychosis in twins discordant for schizophrenia or high-risk individuals, and biomarker studies (12,13,52,53), which aim at uncovering biomarkers for schizophrenia in large cohorts. One advantage…”
Section: Dna Methylationmentioning
confidence: 99%
See 1 more Smart Citation
“…There is also an increasing number of genome-wide DNAm profiling studies of non-central nervous system (CNS) tissues such as blood (12,13,(48)(49)(50)(51)(52)(53) and saliva (54) ( Table 2). These can be further subdivided into longitudinal studies (48)(49)(50)(51)54), which assessed markers of conversion to psychosis in twins discordant for schizophrenia or high-risk individuals, and biomarker studies (12,13,52,53), which aim at uncovering biomarkers for schizophrenia in large cohorts. One advantage…”
Section: Dna Methylationmentioning
confidence: 99%
“…While certain epigenetic modifications in schizophrenia may have a genetic origin (12,13,53,97), converging evidence suggests that a substantial portion of epigenetic alterations may be acquired through environmental factors (98)(99)(100)(101). Hence, epigenetic modifications in schizophrenia may represent molecular scars of exposures to certain environmental adversities, especially when encountered during sensitive developmental periods (102)(103)(104)(105)(106).…”
Section: Epigenetic Modifications As Molecular Scars Of Environmentalmentioning
confidence: 99%
“…Rare variant genetic studies of autism spectrum and bipolar disorders have shown chromatin remodeling genes are more frequently dysregulated among affected individuals [57][58][59][60]. Integration of genetic and epigenetic data has shown that genetic risk variants for ASD, schizophrenia, ADHD, and bipolar disorder control DNA methylation levels more often than non-psychiatric genetic variants [61][62][63][64][65][66][67][68]. Epigenetic changes have also been directly observed in postmortem brain [69][70][71], blood [72][73][74], semen [75,76], saliva [77][78][79], placenta [80], and buccal [81][82][83] tissues in individuals with a psychiatric disorder.…”
Section: Epigeneticsmentioning
confidence: 99%
“…The epigenetic profile is not only influenced by environmental exposure, but likewise seems to be modulated by genetic variants 120 . Evidence is available that SNPs can affect methylation in nearby ( cis ) or distant ( trans ) CpGs, thus supporting the genotype‐epigenotype effect on complex traits 113, 115, 121–124 . Such variants are defined as methylation quantitative trait loci (meQTLs) and could offer some clarification for the unsolved previously identified GWAS polymorphisms.…”
Section: From Genomics To Epigenomicsmentioning
confidence: 99%